MethSCAn: accurate exploratory analysis of single-cell methylomes: research briefing - Kremer, Lukas P. M. (Nature methods, 2024)
Single-cell bisulfite sequencing enables the genome-wide quantification of DNA methylation at single-cell resolution, but methods to analyze the resulting data are lacking. The MethSCAn software accurately distinguishes cell types and states by scanning the genome for informative regions and providing a robust approach to quantifying methylation within these regions.